The Design of The Republic of Indonesia Defense Museum Based on Defense Heritage for the National Interest Through Culture - Francoise, Jeanne; Ary Sulistyo (Green Publisher, 2023)
The research is a derivative program of the Defense Heritage Dissertation by Dr. Jeanne Francoise, with a novelty idea, namely the establishment of the Indonesian Defense Museum. The establishment of the Indonesian Defense Museum aims to narrate the history of Indonesia's national defense in a complete, unified, and comprehensive manner with exhibitions of historical artifacts or objects, sequences of events, involvement of actors, and narratives based on the period of the defense heritage of the Indonesian nation, from 1511 to 1949. This study uses qualitative research methods with analysis obtained from the enrichment of defense heritage theory, cultural diplomacy, defense science, humanities, and museum science, as well as the Focus Group Discussion in Republic of Indonesia’s National Defence Council (WANTANNAS RI) in July 2022. It is hoped that this research can become the main blueprint for the establishment of the Indonesian Defense Museum one day, especially in terms of presenting historical stories in a more interesting and contemporary way, as well as preparing digital literacy to store their collections so that they can continue to be accessed by the public and provide benefits in the academic field.